2018
DOI: 10.1063/1.5049286
|View full text |Cite
|
Sign up to set email alerts
|

Integrating transparent conductive oxides to improve the infrared response of silicon solar cells with passivating rear contacts

Abstract: Abstract. This work addresses the development of a transparent conductive oxide (TCO)/metal stack for n-type Si solar cells featuring a tunnel oxide passivating rear contact (TOPCon). While poly-Si based passivating contacts contacted by local fire-through metallization currently show an increased recombination at the metal contacts and a poor infrared (IR) response, we aim to realize a full-area metallization which maintains the high level of surface passivation and avoids IR losses. Some research groups have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…In particular, this is the case if poly-Si is only a few tens of nanometers thin. [21,22] A PDA at temperatures around 300 C can cure this sputtering damage. [29] Here, we anneal our devices in air after HF treatment and ITO sputtering up to 300 C for 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, this is the case if poly-Si is only a few tens of nanometers thin. [21,22] A PDA at temperatures around 300 C can cure this sputtering damage. [29] Here, we anneal our devices in air after HF treatment and ITO sputtering up to 300 C for 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…We also apply a soft sputtering deposition technique as another way to mitigate sputtering damage, by reducing the plasma UV radiation on the substrate, increasing the path length of particles, and reducing the kinetic energy of the particles hitting the substrate. [ 22–24 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the ρ c values of TMO/p-type c-Si are much lower than those reported from TMO/n-type c-Si, 31,54 and thus, it is safe to state that the hole extraction across the accumulation layer (p-type Si) is more feasible compared to the case of inversion layer (n-type Si). It is worth mentioning that the rear side of the solar cells features micro-pyramids as shown in Figure 2; therefore, the thickness of the thermally evaporated TMO layers on top of the pyramids is expected to be thinner than the thickness measured by SE on polished wafers (by a factor of $0.7) 67 and thus thinner than the thickness used in contact resistivity test structures. Given that the ρ c of Ag/TMO/p-type c-Si decreases with decreasing the TMO thickness, 54 consequently, it can be concluded that in the solar cell, the ρ c of each TMO/Ag layer is slightly lower than those shown in Table 1.…”
Section: Results and Analysesmentioning
confidence: 99%